POLYSYNTHESIS IN THE LANGUAGES OF AMERICAN INDIANS - Manafova, A.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The grammatical structure of the languages of American Indian tribes' languages is based on traditional morphology (the grammatical parts which form words) and syntax (the way words conjoin to form a sentence). It should be emphasized that in grammar, just as in phonological or semantic structures, American Indian languages as well as any other language in the world do not contain anything that could be deemed primitive or underdeveloped. Every language is as complex and efficient as Latin, English, or any other European language. Linguistic processes in the world concern this group of languages. Globalization and integration in the world has led to the rapid standardization and unification of languages, including the American Indians. It is believed that the conservation and disappearance of many languages of the American Indians can be suspended through the written fixation of dialects and dialects, the expansion of the network of primary schools and courses on the study of endangered languages. Of great importance is the social environment in which conditions are created for the preservation of the national-cultural autonomy of certain ethnic groups, including language. An essential role in preserving a language is played by the style of thinking of its carrier.